EVALUATING CONSUMER PURCHASE BEHAVIOR OF CITRALAND RESIDENTIAL MANADO - Kojongian, Brayen Sandy; Sepang, David P.E; Pandowo, Merinda . (Universitas Sam Ratulangi, 2018)
ABSTRACT: The house is a building that serves as the place or residence and mean of gathering the family. Citraland manado, in north sulawesi is a part of Ciputra Group, this company try to introduce modern and elegant housing in North Sulawesi. Citraland has become a renowned housing estate in North Sulawesi especially in Manado, with offers of homes built with trusted architect, beautiful landscape, as well as adequate and guaranteed environmental safety. This resarch aim’s to evaluate the importance and performance of Consumer Purchase Behavior Of Citraland Residential Manado. Consumer behavior is a process on the interaction between customers and producers at the time of purchase the product or services. Based on Consumer Purchase Behavior there are variable within, which is: Structure, Geographical, Environment, and Economic. The sample size of this research is 100 respondents. The result on this study shows that window display placed in quadrant I there are no variables in this quadrant. In quadrant II that shows Structure and Environment in this position. In quadrant III there are Geographical and Economic. While, in quadrant IV there is no variable in this quadrant. So, related with the findings in this research. Keywords: consumer purchase behavior, structure, geographical, environment, economic, importance performance analysis